Detection of genetic markers of pathogenicity factors at associative symbiosis of Klebsiella spp. and Staphylococcus aureus autostrains, isolated from infants - E. V. Bukharova; S. M. Popkova; E. B. Rakova; Y. P. Dzhioev; N. M. Shabanova; U. M. Nemchenko; E. I. Ivanova (Acta Biomedica Scientifica, 2014)
The article presents the results of detection of genetic determinants of pathogenicity in 120 Klebsiella strains (Klebsiella pneumoniae, Klebsiella oxytoca) and 48 Staphylococcus aureus strains isolated from the intestinal habitat of infants with intestinal dysbiosis. Registration of the investigated determinants in Klebsiella spp. autostrains DNA, which are non-clinical isolates, indicates the circulation of pathogenicity factors and, consequently, their possible causation in the formation of intestinal dysbiosis in infants.